Internet of Things Based Computer Laboratory Room Temperature and Humidity Quality Monitoring (Case Study at Institut Teknologi Bisnis AAS Indonesia) - Rokhmah, Siti; Utomo, Ihsan Cahyo (Institut Teknologi Bisnis AAS Indonesia, 2025)
Computer laboratories are important facilities in educational institutions, especially to support technology-based academic activities. However, laboratory environmental management often faces challenges in maintaining ideal temperature and humidity stability, which can affect hardware performance and life. This study aims to design and implement a temperature and humidity quality monitoring system for a computer laboratory room based on the Internet of Things (IoT) at the AAS Indonesia Business Technology Institute. The developed system utilizes temperature and humidity sensors integrated with an IoT platform for real-time data collection, processing, and presentation. Environmental data is monitored through a cloud-based application, which is equipped with automatic notifications if abnormal conditions occur, such as high temperatures or humidity outside the ideal limits. System testing shows that this technology is able to provide accurate and continuous monitoring, and helps make faster decisions in managing the laboratory environment. The results of the study show that the application of an IoT system in monitoring temperature and humidity improves the efficiency of laboratory management while supporting the principle of energy efficiency. This system also provides easy access to data remotely, thereby minimizing the risk of device damage. With effective implementation, this study not only provides a practical solution for laboratory facility management but also makes a significant contribution to driving digital transformation in the education sector.